Management of Root-Knot Nematodes with Chemical and Nonchemical Pesticides of Tomato under Protected Cultivation - Ghimire, Prakash; K.C., Gopal Bahadur; Shrestha, Ram Kumar; Shapkota, Dinesh (Journal of the Plant Protection Society, 2024)
Protected (plastic house) cultivation offers numerous advantages for vegetable production in Nepal. Continuous cropping cycles within soil-based closed structures have led to a rise in soil-borne pathogens, notably in the mid-hills of Nepal, posing challenges to sustainable crop production. Root-knot nematodes (RKNs) particularly threaten protected cultivation, demanding significant time and financial investments for effective management. This study has investigated the efficacy of chemical (fosthiazate) and non-chemical (biogas slurry, Trichoderma sp., neem cake, and root care) pesticides with an untreated control for RKN management in tomato grown under plastic houses. A randomized three-block trial was conducted to compare the effectiveness of the treatments. Results revealed significant differences in the galling index (GI), demonstrating that fosthiazate, neem cake, and biogas slurry outperformed the control. In pairwise mean comparison, fosthiazate, neem cake, and biogas slurry were superior to the control with GI of 2.23%, 2.67%, and 3.23%, respectively, where the control had an average GI of 4.45%. There was no significant difference between fosthiazate and neem cake in the galling index, while the performance of Trichoderma and root care (a commercial product produced from the combination of organic raw materials) showed no significant difference compared to the control in remediating RKN-induced root galling in tomato. All other treatments gave significantly lower disease incidence than the control. The lowest disease incidence was found to be 12.23 ± (4.10)% and the lowest galling index was 2.23 ± (0.74) % with the application of fosthiazate, followed by neem cake with 16.67 ± (5.56)% disease incidence and 2.67 ± (0.89)% galling index, while the control had the highest disease incidence (80.0 ± (26.67)%. These findings suggest the best management option that may be promising prospects for environment-friendly management of RKN in protected tomato cultivation under plastic houses.